Influence of political communication on the transformation of identity. Reflection in Ukrainian digital media discourse - Nosova, Bogdana (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
This article has been updated due to the new processes present in the Ukrainian digital media discourse. The texts that were published in the Ukrainian digital media from 2013–2015 actively covered the problem of the transformation in Ukrainian identity. The article aims to show the role of digital media in the transformation of the Ukrainian identity. To this end, an overview of modern interpretations in the media of Ukrainian identity is given; the catalyzing impact of digital media on the transformation of Ukrainian identity is shown; and it is demonstrated that the European integration dialogue within the Eastern Partnership is stimulating the transformation of Ukrainian identity (using texts from convergent media, such as the “Den” [Day] newspaper).The theoretical basis of this article deals with the works of renowned scholars in the field of the impact of digital media on various social changes. This includes researchers such as Jim Hall on online journalism, Volodymyr Kulyk on the objectivity of digital media, Richard A. Lanham on the importance of the “electronic word” and Andrzej Mencwel on the tools of the multimedia communication revolution. Identity issues are raised in the article on the theoretical basis of Monserrat Guibernau, Yaroslav Hrytsak and Zenon E. Kohut. The mobilizing impacts of digital media on society are reflected in the texts on the Ukrainian Euromaidan and Dignity Revolution period published in traditional media and distributed online. The authors of these digital media include historian, Timothy Snyder, writer, Oksana Zabuzhko, and online communications expert, Maksym Savanevsky. The use of digital media in political communications has led to new demonstrations of Ukrainian identity and its adaptation to new political realities. Digital media were at the forefront of operational information about the events of the political life of the state. Political, social and state institutions have focused on communication with citizens over the Internet, including social media, blogs and columns in online media. The high-quality digital media used in Ukraine have taken on an innovative position of pluralism, ultimately adapting to a European national identity, or at least cruising along a parallel trajectory with Europe. The European integration dialogue within the Eastern Partnership in the media has been stimulating the transformation of the Ukrainian identity. Other new projects, which include publishing of books based on digital media texts, are also essential. The Ukrainian high-quality digital media, maintaining the traditions of free media, have reached a high level in analyzing the facts truthfully and adequately reflecting Ukraine’s political processes and its involvement in international events.

Artykuł przedstawia nowe procesy obecne w ukraińskim dyskursie mediów cyfrowych. Teksty opublikowane w ukraińskich mediach cyfrowych w latach 2013–2015 aktywnie zajmowały się problemem transformacji ukraińskiej tożsamości, a celem artykułu jest ukazanie ich roli w tej transformacji. W tym celu przedstawiono przegląd współczesnych medialnych interpretacji ukraińskiej tożsamości, pokazano katalizujący wpływ mediów cyfrowych na jej transformację i pokazano, że dialog na temat integracji europejskiej w ramach Partnerstwa Wschodniego stymuluje transformację ukraińskiej tożsamości (z wykorzystaniem tekstów z mediów konwergentnych, takich jak gazeta „Den” [Dzień]). Teoretyczne podstawy tego artykułu stanowią prace wybitnych uczonych w zakresie wpływu mediów cyfrowych na różne zmiany społeczne. Dotyczy to takich badaczy jak Jim Hall w dziedzinie dziennikarstwa internetowego, Wołodymyr Kulyk w dziedzinie obiektywizmu mediów cyfrowych, Richard A. Lanham zajmujący się tym jak ważne jest „słowo elektroniczne” i Andrzej Mencwel mówiący o narzędziach rewolucji komunikacji multimedialnej. Kwestie tożsamości zostały poruszone w artykule na podstawie teorii Monserrat Guibernau, Jarosława Hrytsaka i Zenona E. Kohuta. Mobilizujący wpływ mediów cyfrowych na społeczeństwo znajduje odzwierciedlenie w tekstach ukazujących się w czasie trwania ukraińskiego Euromajdanu i „rewolucji godności” w mediach tradycyjnych i internetowych. Autorami tekstów publikowanych w mediach cyfrowych są historyk Timothy Snyder, pisarka Oksana Zabużko i ekspert w zakresie komunikacji internetowej, Maksym Savanevsky. Wykorzystanie mediów cyfrowych w komunikacji politycznej wykształciło nowe przejawy tożsamości ukraińskiej i dostosowało ją do nowych realiów politycznych. Media cyfrowe znalazły się w czołówce mediów informujących o wydarzeniach z życia politycznego państwa. Instytucje polityczne, społeczne i państwowe koncentrują się na komunikacji z obywatelami za pośrednictwem Internetu, w tym mediów społecznościowych, blogów i kolumn w mediach internetowych. Wysokiej jakości media cyfrowe wykorzystywane na Ukrainie zajęły innowacyjne stanowisko pluralistyczne, dostosowując się do europejskiej tożsamości narodowej lub przynajmniej idąc w tym samym co reszta Europy kierunku. Prowadzony w mediach dialog na temat integracji europejskiej w ramach Partnerstwa Wschodniego stymuluje transformację ukraińskiej tożsamości. Istotne są również inne nowe projekty, w tym publikacja książek opartych na tekstach pochodzących z mediów cyfrowych. Ukraińskie media cyfrowe wysokiej jakości, podtrzymując tradycje wolnych mediów, osiągnęły wysoki poziom odpowiadającej prawdzie analizy faktów i adekwatnie odzwierciedlają procesy polityczne na Ukrainie i jej zaangażowanie w wydarzenia międzynarodowe.
Wpływ komunikacji politycznej na transformację tożsamości: refleksja w ukraińskim dyskursie mediów cyfrowych
Keywords: communication; komunikacja; identity; tożsamość; information; informacja; digital media; media cyfrowe